Hamlyn junior encyclopedia - Burton,Robert (Hamlyn Books London, 1992)
This general encyclopedia includes information on technological advances, wildlife - fauna and flora - geographical and architectural features of the world, archeological and historic sites as well as information on major writers, politicans and public figures.